Regenerative properties of bone marrow mesenchymal stem cell derived exosomes in rotator cuff tears - Junjie Chen; Zihe Wang; Ming Yi; Yi Yang; Mengzhao Tian; Yinqi Liu; Guoyou Wang; Huarui Shen (Journal of Translational Medicine)
Abstrct Rotator cuff injury (RCI), characterized by shoulder pain and restricted mobility, represents a subset of tendon-bone insertion injuries (TBI). In the majority of cases, surgical reconstruction of the affected tendons or ligaments is required to address the damage. However, numerous clinical failures have underscored the suboptimal outcomes associated with such procedures. Further investigations have revealed that these failures are largely attributable to delayed healing at the tendon-bone interface, excessive formation of vascularized scar tissue, and inadequate integration of tendon grafts within bone tunnels. As a result, the healing process of rotator cuff injuries faces significant challenges.Bone marrow-derived mesenchymal stem cell exosomes (BMSC-exos) have emerged as a prominent focus of research within the field of bioengineering, owing to their remarkable potential to regulate cellular proliferation and differentiation, modulate immune responses, and facilitate tissue repair and regeneration following cellular damage. In this review, we explore the anti-inflammatory, angiogenic, anti-scarring, and bone metabolism-modulating effects of BMSC-exos in the context of rotator cuff injury. Additionally, we address the limitations and ongoing challenges within current research, offering insights that could guide the clinical application of BMSC-exos in the treatment of rotator cuff injuries in the future.